Multi-Key Searchable Encryption with Designated Server. Issue 2 (2nd April 2016) - Zhou, Yousheng; Guo, Han; Wang, Feng; Luo, Wenjun
Abstract: This paper presents a novel multi-key searchable encryption with designated server based on the RA Popa's multi-key searchable encryption and Rhee's PEKS. As far as we know, it is the first multi-key searchable encryption based on asymmetric cryptographic approach. One advantage of our proposed scheme is that it allows a user to provide a single trapdoor to the server, though it allows the designated server to search for that trapdoor's word in documents encrypted with different keys. Another advantage of our scheme is that only the designated server can identify whether a trapdoor matches the encrypted data or not.